Survivor's guide to small business - Townsley, Maria (Thomson South-Western, 2003)
Designed for those who need to know the basics, this text will guide users through the world of small business and the skills needed to survive. This comprehensive, easy-to-use guide for small business development and ownership reflects the most current topics and issues that entrepreneurs face in an easy to understand manner